The relationship between self-efficacy and academic performance - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
Most researchers investigating the relationship between self-efficacy and performance have reported a strong correspondence (Pajares and Miller, 1994). The aim of this study is to investigate relationships between self-efficacy and academic performance among a sample of 82 sophomore students who attended Instructional Planning and Evaluation class at the Marmara University Technical Education Faculty. Survey method used in this research. Each student's final grade note was used as a performance measure. The instrument was used to measure self-efficacy is the Motivational Strategies Scale developed by Pintrinch and De Groot (1990) and adapted into Turkish by Altun and Erden (2006). Data analyzed by Pearson's Correlation and descriptive statistics. Findings were discussed regarding to the literature.
Keywords: MSLQ; Academic performance; Self-efficacy; Material design; Instructional Planning and Evoluation